Rules for stealing stars - Haydu, Corey Ann (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2015)
Silly is used to feeling left out. Her three older sisters think she's too little for most things -- especially when it comes to dealing with their mother's unpredictable moods and outbursts. This summer, Silly feels more alone than ever when her sisters keep whispering and sneaking away to their rooms together, returning with signs that something mysterious is afoot: sporting sunburned cheeks smudged with glitter and gold hair that looks like tinsel. When Silly is brought into her sisters' world, the truth is more exciting than she ever imagined. The sisters have discovered a magical place that gives them what they truly need: an escape from the complications of their home life. But there are dark truths there, too. Silly hopes the magic will be the secret to saving their family, but she's soon forced to wonder if it could tear them apart.
Ages 8-12.
Middle School.
Accelerated Reader
Reading Counts!
720
Keywords: Sisters -- Juvenile fiction; Magic -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Children of alcoholics -- Juvenile fiction; Family secrets -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Sisters -- Fiction; Magic -- Fiction; Family problems -- Fiction; Sick -- Fiction; Mothers and daughters -- Fiction; Fantasy fiction